Pengaruh Insentif, Fasilitas Kerja, Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada Hotel Sahid Jaya di Surakarta - Prima Prihatini; Anggun Ayu Salianti Putri; Destina Paningrum (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2022)
The purpose of this study was to analyze the effect of incentives, work facilities, and career development on employee performance. The object of this research is at Hotel Sahid Jaya Surakarta. The hypothesis of this study is that incentives, work facilities, and career development have a positive and significant effect on the performance of Sahid Jaya Hotel employees in Surakarta. The number of samples in this study were 120 respondents who were obtained by using purposive sampling, namely the technique of determining the sample by using special characteristics that are in accordance with the research objectives so that it is expected to be able to answer research problems. Then the method of data collection through questionnaires and data analysis using SPSS which includes validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing using t test, R² test. The results showed that the independent variables, namely incentives (X1), work facilities (X2), and career development (X3) had a positive and significant effect on employee performance (Y) partially or simultaneously (together). Based on the coefficient of determination of 0.516, it is known that incentives, work facilities, and career development affect employee performance variables by 51.6% while the remaining 48.4% is influenced by other variables not described in this study.